Investigating In Vitro and Ex Vivo Properties of Artemether/Lumefantrine Double-Fixed Dose Combination Lipid Matrix Tablets Prepared by Hot Fusion - Christi A. Wilkins; Lissinda H. du Plessis; Joe M. Viljoen (MDPI AG, 2021)
Highly lipophilic antimalarial drugs, artemether and lumefantrine, whilst an effective fixed-dose combination treatment to lower the malarial disease burden, are therapeutically hindered by low aqueous solubility and varied bioavailability. This work investigates the plausibility of directly compressed lipid matrix tablets, their role as lipid-based formulations and their future standing as drug delivery systems. Lipid matrix tablets were manufactured from solid lipid dispersions in various lipid:drug ratios employing hot fusion-the melt mixing of highly lipophilic drugs with polymer(s). Sequential biorelevant dissolution media, multiple mathematical models and ex vivo analysis utilizing porcine tissue samples were employed to assess drug release kinetics and more accurately predict in vitro performance. Directly compressed stearic acid tablets in a 0.5:1 lipid:drug ratio were deemed optimal within investigated parameters. Biorelevant media was of immense value for artemether release analysis, with formulation SA0.5C1 (Stearic Acid:double fixed dose in a 0.5:1 ratio (i.e., Stearic acid 70 mg + Lumefantrine 120 mg + Artemether 20 mg); CombiLac® as filler (q.s.); and 1% w/w magnesium stearate) yielding a higher percentage of artemether release (97.21%) than the commercially available product, Coartem® (86.12%). However, dissolution media lacked the specificity to detect lumefantrine. Nonetheless, stearic acid lipid:drug ratios governed drug release mechanisms. This work demonstrates the successful utilization of lipids as pharmaceutical excipients, particularly in the formulation of lipid matrix tablets to augment the dissolution of highly lipophilic drugs, and could thus potentially improve current malarial treatment regimens.